In silico Evolutionary Divergence Analysis Suggests the Potentiality of Capsid Protein VP2 in Serotype-Independent Foot-and-Mouth Disease Virus Detection - Mishu, Israt Dilruba; Akter, Salma; Alam, A. S. M. Rubayet Ul; Hossain, M. Anwar; Sultana, Munawar (Frontiers in Veterinary Science, 2020)
Foot-and-mouth disease (FMD) is an economically devastating disease of livestock population caused by FMD virus (FMDV) which has seven immunologically distinct serotypes (O, A, Asia1, C, SAT1-SAT3). Studies suggest that VP2 is relatively conserved among three surface exposed capsid proteins (VP1-VP3) of FMDV, but the level of conservancy has not been reported yet. Here, we analyzed the comparative evolutionary divergence of VP2 and VP1 to determine the level of conservancy in VP2 at different hierarchical levels of three FMDV serotypes (O, A and Asia1) currently circulating in Asia through in-depth computational analysis of 14 compiled datasets and designed a consensus VP2 protein that can be used for the development of a serotype independent FMDV detection tool. Phylogenetic analysis conferred a significant level of conservancy in VP2 over VP1 at each subgroup level. Protein variability analysis and mutational study showed presence of 67.4% invariant amino acids in VP2 with higher conservancy in the N terminal end. Nine inter-serotypically conserved fragments located on VP2 have been identified among which four sites were found that showed promising antigenicity value and surface exposure. The designed 130 amino acid long consensus VP2 protein was found to possess six surface exposed B cell epitopes which suggests the possible potentiality of the protein for the development of a serotype independent FMDV detection tool in Asia. Conclusively, this is the first study reporting comparative evolutionary divergence between VP2 and VP1, along with proposing the possible potentiality of a designed protein candidate in serotype independent FMDV detection.